Effects of inspired oxygen fractions in rabbits anesthetized with isoflurane or sevoflurane, maintained on spontaneous ventilation - M. Horr (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT It is important to identify the best inspired fraction of oxygen in a variety of situations, including sevoflurane or isoflurane anesthesia, in spontaneously breathing rabbits. For this, 64 rabbits were assigned to eight groups: GI100 (FiO2= 1,0 + isoflurane), GS100 (FiO2= 1,0 + sevoflurane), GI80 (FiO2= 0,8 + isoflurane), GS80 (FiO2= 0,8 + sevoflurane), GI60 (FiO2= 0,6 + isoflurane), GS60 (FiO2= 0,6 + sevoflurane), GI21 (FiO2= 0,21 + isoflurane), GS21 (FiO2= 0,21 + sevoflurane). The induction was performed with (2.5MAC) of the anesthetic. The vaporizer was setted at 1.5 MAC and FiO2 as attributed for each group. After the induction, the concentration was changed to 1 MAC. Measurements of parameters were performed 30 minutes after induction (T0), and then at 15 minute intervals (from T15 to T60). The arterial partial pressures of oxygen (PaO2), alveolar oxygen partial pressure (PAO2) and alveolar-arterial oxygen gradient [P(A-a)O2] were higher with the use of high FiO2. The GI80 showed higher levels of PaO2 FiO2 ratio and respiratory index (RI). In conclusion, the FiO2 of 0.21 is not indicated, because it causes hypoxemia. The isoflurane determines better ventilation when compared to sevoflurane, but isoflurane associated with 80% of oxygen promotes intrapulmonary shunt increase.